Bioaccumulation of heavy metals in high Andean crops of the Peruvian Andes: comparative evaluation between irrigated and dry systems - Ccopi Trucios, Dennis (2025)
Heavy metal contamination in Andean agricultural systems is a growing concern for food safety and environmental health. This study assessed the concentrations and bioaccumulation patterns of eleven metals (Cd, Pb, As, Cr, Ni, Cu, Zn, Mn, Fe, Hg, Mo) in seven representative crops cultivated under irrigated and rainfed conditions in the Mantaro Valley, central Peruvian Andes. Soil and foliar samples were collected from paired plots, and bioaccumulation factors (BAF) were calculated to evaluate metal transfer to plant tissues. Irrigated soils showed higher and more homogeneous concentrations of Cd, Pb, and As, reflecting long-term accumulation from historical mining activities and irrigation with contaminated water from the Mantaro River. Foliar concentrations exceeded Codex Alimentarius limits for Cd, Pb, and As in several crops, especially potato and broad bean. BAF analyses revealed distinct crop-specific behaviors: potato, quinoa, and broad bean frequently exhibited BAF >1 for metals such as Cd, Cu, Zn, and Mn, indicating active uptake and translocation. In contrast, cereals such as maize and barley maintained low BAF values (<1), suggesting conservative absorption patterns. Irrigation increased the bioavailability of several metals, resulting in higher foliar concentrations and elevated BAF values compared to rainfed systems. Multivariate analyses further differentiated metal accumulation profiles by crop type and water management system. These findings highlight the need for strengthened monitoring of high-accumulation crops and improved soil and water quality management in historically contaminated Andean agricultural regions.